GROWING ENVIRONMENTAL LITERACY TOWARDS ADIWIYATA SCHOOLS THROUGH NATURAL SCIENCE LEARNING BASED ON PEDAGOGY FOR SUSTAINABILITY - Susilowati Susilowati; Insih Wilujeng; Purwanti Widhy Hastuti (Journal of Science Education Research, 2018)
Environmental awareness is an issue that continues to evolve with the development of science and technology. Various problems that arise include attitudes to protect the environment, to choose a healthy lifestyle, to utilize natural resources, to deal with natural disasters, and to concern about the rising global temperatures. The government carries out the Adiwiyata school program with the aim to instill values of environmental awareness for students. This leads to the importance of building environmental literacy to direct in building the environmentally-aware attitude that supports the preparation to become Adiwiyata schools. Learning based on sustainability (pedagogy for sustainability) has the potential to be integrated in science learning, considering that natural science subjects examine natural phenomena and the symptoms physically, chemically, and biologically as well as the relation to technology, environment, and society. Attitudes and actions towards environmental literacy can be inculcated through the development of learning processes containing pedagogy for sustainability that emphasizes activities to seek, explore, discuss, and investigate information and also to plan actions that are beneficial to the environment and do not carry any negative impacts on future generations.